STRATEGI KOMUNIKASI PUSTAKAWAN DAN PEMUSTAKA DALAM MENCARI SUMBER INFORMASI DI PERPUSTAKAAN - Armen Armen (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2017)
From a religious perspective, we can easily answer that it is God who teaches us to communicate, using the intellect and language skills that are bestowed upon us. The Qur'an says, "God is most gracious, who has taught the Qur'an. He created man, who taught him how to speak "(Ar-Rahman: 1-4). Speaking of communication definitions, there is no right or wrong definition. Like any model or theory, definitions must be seen from their usefulness to explain the phenomena that are defined and evaluate them. Maybe too narrow, for example "Communication is the delivery of messages through electronic media or too broad for example Communication is the interaction between two or more living things". Communication is broadly defined as sharing experiences to some extent, each being can be said to communicate in terms of sharing experiences. Human communication in English is Human communication. All Beings, institutions or institutions large and small all need good communication.